When income isn't a factor, what makes Kuala Lumpur's upper-class (T20) households happy? the role of generosity and social support - Burhan, Nik Ahmad Sufian; Sabri, Mohamad Fazli; Baharuddin, Najwa; Hamsan, Hanina H.; Charansarn, Arina (Malaysian Consumer and Family Economics Association, 2024)
Easterlin Paradox theory suggests that individuals with the highest incomes do not get happier as they get richer. If this is the case for Malaysians, what else can bring them happiness? This study adopted the World Happiness Report (WHR) research paradigm to examine the impact of generosity and social support on the happiness of 334 individuals from high-income households (T20) in Kuala Lumpur. The data were collected using a homogeneous convenience sample method and analyzed with robust regressions. Results revealed that while income increases from T1 to T2 had non-significant impact on happiness among T20s, generosity and social support had significant positive effects. Finally, our findings imply that policymakers should create policies that promote individuals to help one another socially and be more generous to those in need. This approach may increase societal social capital and happiness even further.